1987
DOI: 10.4315/0362-028x-50.7.543
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Resistance of Listeria monocytogenes in Dairy Products

Abstract: The thermal resistance of Listeria monocytogenes strain Scott A that had been associated with a recent milkborne outbreak of listeriosis was determined in whole and skim milk, heavy cream, and ice cream mix. L. monocytogenes suspended at concentrations of approximately 1 × 105 cells/ml was heated at temperatures ranging from 52.2 to 79.4°C at various contact times. The D71.7°C values computed for milk samples ranged from 0.9 to 2.7 s. The D7.94°C value in ice cream mix was 0.5 s. The zD value for fluid product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
1
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 0 publications
3
16
1
1
Order By: Relevance
“…The z values of 6.5 (Bradshaw et al 1987), 7.3 (Bunning et al 1986), 8.0 (Bunning et al 1988, and 6.3 (Bradshaw et al 1985) were reported for L. monocytogenes in milk. The apparent difference of the z value of the present study from other reported studies could be attributed to the food system used in the experiments.…”
Section: Determination Of Z Value For L Monocytogenes Using the Thermentioning
confidence: 99%
See 3 more Smart Citations
“…The z values of 6.5 (Bradshaw et al 1987), 7.3 (Bunning et al 1986), 8.0 (Bunning et al 1988, and 6.3 (Bradshaw et al 1985) were reported for L. monocytogenes in milk. The apparent difference of the z value of the present study from other reported studies could be attributed to the food system used in the experiments.…”
Section: Determination Of Z Value For L Monocytogenes Using the Thermentioning
confidence: 99%
“…The differences, in the observed D value in the present study and reported D values, are once again due to the different milk food systems used in the respective experiments. Some scientists used skim milk (Bradshaw et al 1987), whereas other scientists used whole milk (Bunning et al 1988) in thermal resistance studies. Sterile whole milk was used in the present study as well.…”
Section: Determination Of the Decimal Reduction Time (D) For L Monocmentioning
confidence: 99%
See 2 more Smart Citations
“…monocytogenes bulunduğundan, besin maddelerinin bulaşı daima söz konusu olabilmektedir (6,10). Sığır, koyun ve kümes hayvanları ile kuşlardan elde edilen, L. monocytogenes, temel gıda maddeleri olan et ve et ürünlerinde kolaylıkla gelişebilmekte, gıda endüstrisi çalışan-larında problemler oluşturmaktadır (5,10,15,19,24,32).…”
unclassified